JEJAK EVOLUSI BAHASA SASAK: ANALISIS HISTORIS DAN PERKEMBANGANNYA - Chaer, Hasanuddin; Pratama R., Januari Rizki; Efendi , Mahmudi; Khairussibyan, Muh.; Ashriany, Ratna Yulida; Wahyuni, Wika (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This article aims to analyze the evolutionary trajectory of the Sasak language using a historical approach and the language evolution theory developed by Schleicher. This theory depicts languages as entities undergoing evolution similar to biological organisms, evolving from simple forms to complex forms through natural selection. To achieve this, the research methodology includes literature review, primary data collection, historical analysis, and an examination of the development of the Sasak language within the contexts of social, educational, and modern media environments. Consequently, this article utilizes Schleicher’s tree diagram to illustrate the genetic relationships and linguistic changes within the Sasak language on Lombok Island. The implications of this research provide a deeper understanding of the evolution of the Sasak language and the factors influencing it.